Exploring Consumer and Clinician Attitudes towards Patient Reported Outcome Measures (PROMs) in an Australian Inpatient Musculoskeletal Rehabilitation Unit: A Qualitative Pilot Study - Rehana Di Rico; Louisa Ng; Jacquelin Capell (Patient Experience Journal)
Objective: This pilot qualitative study explores consumers' and clinicians' perspectives about the relevance and utility of patient reported outcome measures (PROMs) in an Australian inpatient rehabilitation unit. Methods: Two focus groups, were recruited via convenience sampling, comprising English speaking rehabilitation clinicians (n = 5) and consumers (n = 6) who had recent experience of inpatient musculoskeletal rehabilitation in a large, privately funded, rehabilitation hospital in Melbourne Australia, in 2020. The focus groups were conducted via videoconference, moderated by two experienced rehabilitation clinician-researchers, following semi-structured interview guides. Focus group recordings were professionally transcribed for coding and thematic analysis by two researchers, with consensus reached about final themes. Results: Rehabilitation clinicians and consumers identified potential utility in measuring PROs at the patient level to improve patient-centred care and team coordination, and at the system level through quality improvement, benchmarking and research. Benefits were viewed as contingent on a clearly articulated rationale for measurement, careful selection of PRO instruments and specific application in target populations, with doubts expressed over their specific utility in musculoskeletal rehabilitation. Risks associated with PROMs were also identified, including procedural burden, emotional distress, psychological safety, incomplete forms and opportunity-cost. Clinicians and consumers expressed concern over the validity, reliability and representativeness of PROM data. Conclusions: While the potential benefits of PROMs were recognised, numerous risks and logistical challenges were also identified. The current lack of confidence from both clinicians and consumers in the inherent value of PROM data and its ability to improve patient care or quality standards will likely impede successful incorporation into routine rehabilitation care.